ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE CAMEL PADA LAPORAN KEUANGAN PT. BANK SYARIAH INDONESIA TAHUN 2021-2024 - Umairoh, Nisa Ul Anda; Khayati, Ismatul (Jurnal Manajemen dan Bisnis, 2026)
Thisl study aims lto determine lthe health llevel of lPT. Bank lSyariah Indonesia (lBSI) Tbk inl 2021-2024. The assessmentl indicators usedl in lthis study lare Capital, lAsset Quality, lManagement, Earning, andl Liquidity lor abbreviated las CAMEL. Thel Camel methodl is one of the factors lthat greatly ldetermines the healthl of la bank. Thisl study wasl conducted withl a lquantitative descriptive lapproach, namely usingl secondary ldata obtained lfrom library sources such as academic journals, government publications and annual lfinancial reports published lon the lcompany's officiall website, lby analyzing lthe CAR, lNPF, PDN, lROA, ROE, lBOPO, NI, land FDR lratios. The resultsl of thel study lshowed that lthe CAR lratio for the 2021-2024 periodl was given the predicatel "very lhealthy". The lNPF ratio lfor the 2021-2023l period was given thel predicate "lhealthy", whilel in 2024 lit was lgiven the lpredicate "veryl healthy". lThe PDN ratiol for thel 2021-2024 period lwas given lthe predicate "quite lhealthy". The ROAl ratio lin 2021-2024 was givenl the lpredicate "very healthy". lThe ROE lratio in 2021-2024 lwas given lthe predicate "lhealthy". The BOPO ratio in 2021-2024 lwas given lthe predicate "veryl lhealthy". The lNI ratio lin 2021-2024 lwas given lthe predicate "lhealthy". The lFDR ratio lin 2021 was lgiven the lpredicate "very lhealthy". However, inl 2022-2024 itl decreased and was givenl the lpredicate "healthy". lThe findings show lthat based lon these lindicators, the performance of Bank Syariahl Indonesial lTbkl in 2021-2024 was on average in the "very healthy" category, which indicates goodl financial health laccording to lthe overall lassessment.